Jawabanmu

2014-08-18T21:59:53+07:00
1. 3y² + 2y - 4 + ( -6y² - 2y + 6 ) = 3y²+ 2y - 4 - 6y² - 2y + 6
                                               = -3y²+2 atau 2-3y²
2. -3x - y + 2 + x + 7y - 5z = -2x + 6y - 5z + 7y
3. 2x² + X - 3 + ( -4x² + 2x + 1) = 2x² + x - 3 - 4x² + 2x + 1
                                              = 3x - 2x² - 2
2014-08-18T22:32:42+07:00
3y² + 2y - 4 - (-6y²) - 2y + 6
3y² + 6y² + 2y - 2y - 4 + 6
9y² + y + 2

-3x - y + 2 - x + 7y - 52
-3x - x - y + 7y + 2 - 52
-4x + 6y - 50

2x² + x - 3 - (-4x²) + 2x + 1
2x² + 4x² + x + 2x - 3 + 1
6x² + 3x - 2